Analyzing the causal relationship between exchange rate and international tourism in Vietnam - Le, Nu Minh Phuong; Tran, Doan Thanh Thanh (Journal of International Economics and Management, 2024)
The impact of tourism on exchange rates, and vice versa, varies from country to country. This study empirically explores the causal relationship between exchange rates and international tourism in Vietnam. To examine this relationship, data on real exchange rates, foreign tourist arrivals, and real tourism revenue were extracted from the general statistical yearbook from 2000 to 2019. This paper explicitly highlights how exchange rates impact tourism under a government-controlled exchange rate regime. The results indicate a weak unidirectional causal relationship between foreign tourist arrival and real exchange rates. An increase in the real exchange rate increases short-term income but has a negative impact on long-term tourism revenue, while an increase in real tourism revenue reduces the real exchange rate in the short run but is stable in the long run. The research supports the perspective that maintaining a stable exchange rate attracts international tourists in the long term. Based on these findings, the Vietnamese government should adopt a cautious approach to price stabilization policies and encourage export-oriented industries to attract international tourists and promote tourism.